Q-switched thulium-doped fiber laser operating at 1920 nm region with multiwalled carbon nanotubes embedded in polyvinyl alcohol - Ahmad, M.T.; Abdul Latiff, Anas; Zakaria, Zahriladha; Zen, D.I.M. (Wiley, 2014)
We demonstrate a Q-switched Thulium-doped fiber laser operating at approximately 1912 nm region using multiwalled carbon nanotubes (MWCNT) embedded in polyvinyl alcohol (PVA) as the passive saturable absorber (SA). The SA is fabricated by mixing the dispersed MWCNTs suspension into a PVA solution MWCNT and let the precursor to dry in the room temperature to form the film. The film is sandwiched between two FC/PC fiber connectors before it is incorporated in a ring laser cavity to produce self-started pulse train with repetition rate that can tuned from 13.07 to 21.67 kHz as the 1552 nm pump power is increased from 302 to 382 mW. At 382 mW pump, the Q-switched laser has a pulse width of 7.93 µs and pulse energy of 103.37 nJ.